Radioisotope-Guided Sentinel Lymph Node Biopsy in Penile Cancer: A Long-Term Follow-Up Study - Nemitz, Lena; Vincke, Anna; Michalik, Bianca; Engels, Svenja; Meyer, Luca-Marie; Henke, Rolf-Peter; Wawroschek, Friedhelm; Winter, Alexander (Frontiers in Oncology, 2022)
Lymph node (LN) management is critical for survival in patients with penile cancer. However, radical inguinal lymphadenectomy carries a high risk of postoperative complications such as lymphedema, lymphocele, wound infection, and skin necrosis. The European Association of Urology guidelines therefore recommend invasive LN staging by modified inguinal lymphadenectomy or dynamic sentinel node biopsy (DSNB) in clinically node-negative patients (cN0) with intermediate- and high-risk tumors (≥ T1G2). However, the timing of DSNB (simultaneous vs. subsequent to partial or total penile resection) is controversial and the low incidence of penile cancer means that data on the long-term outcomes of DSNB are limited. The present study aimed to analyze the reliability and morbidity of DSNB in patients with penile cancer during long-term follow-up. This retrospective study included 41 patients (76 groins) who underwent radioisotope-guided DSNB simultaneously or secondarily after penile surgery from June 2004 to November 2018. In total, 193 sentinel LNs (SLNs) and 39 non-SLNs were removed. The median number of dissected LNs was 2.5 (interquartile range 2–4). Histopathological analysis showed that five of the 76 groins (6.6%) contained metastases. None of the non-SLNs were tumor-positive. In accordance with the guidelines, all inguinal regions with positive SLNs underwent secondary radical inguinal lymphadenectomy, which revealed three additional metastases in one groin. Regional LN recurrence was detected in three patients (four groins) during a median follow-up of 70 months, including two patients in whom DSNB had been performed secondarily after repetitive penile tumor resections. DSNB-related complications occurred in 15.8% of groins. Most complications were mild (Clavien–Dindo grade I; 50%) or moderate (II; 25%), and invasive intervention was only required in 3.9% of groins (IIIa: n = 1; IIIb: n = 2). In summary, this study suggests that the current radioisotope-guided DSNB procedure may reduce the complication rate of inguinal lymphadenectomy in patients with cN0 penile cancer. However, DSNB and penile surgery should be performed simultaneously to minimize the false-negative rate. Recent advances, such as new tracers and imaging techniques, may help to reduce the false-negative rate of DSNB further.